An educational analysis on the legal protection of inventions in the European Union: past and present - Belikova, Ksenia Michailovna (2020)
This article aims to explore the developments in the legal protection of inventions in the European Union (EU) from the perspective of regulatory measures on the matter and the rules of procedure in order to identify appropriate regulatory models. Based on analytical reflections on the information obtained from relevant sources and literature and dialectic method, the author analyzes the provisions of the EU regulations that create patterns of legal framework and patent protection from the point of view of consolidating the novels of substantial legislation and practice and procedural. The article is based on analytical reflections on information taken from sources and literature and descriptive approach to the legal regulations in the field under study. The results are presented in a system and comparison of the protection regimes - current and previous - of patent rights in the EU. Thus, the theoretical and practical importance of the results obtained is determined by the fact that the reader will have modern scientific information on the state of EU legislation in the field under study, which will contribute to understanding the gap (or your absence). on the achievements of researchers and professionals in Russia and abroad in this area.